Novel ultra-high-frequency electrocardiogram tool for the description of the ventricular depolarization pattern before and during cardiac resynchronization - Jurak, Pavel; Curila, Karol; Leinveber, Pavel; Prinzen, Frits W; Viscor, Ivo; Plesinger, Filip; Smisek, Radovan; Prochazkova, Radka; Osmancik, Pavel; Halamek, Josef; Matejkova, Magdalena; Lipoldova, Jolana; et al. (Journal of cardiovascular electrophysiology, 2020)
INTRODUCTION: The present study introduces a new ultra-high-frequency 14-lead electrocardiogram technique (UHF-ECG) for mapping ventricular depolarization patterns and calculation of novel dyssynchrony parameters that may improve the selection of patients and application of cardiac resynchronization therapy (CRT). METHODS: Components of the ECG in sixteen frequency bands within the 150 to 1000 Hz range were used to create ventricular depolarization maps. The maximum time difference between the UHF QRS complex centers of mass of leads V1 to V8 was defined as ventricular electrical dyssynchrony (e-DYS), and the duration at 50% of peak voltage amplitude in each lead was defined as the duration of local depolarization (Vd). Proof of principle measurements was performed in seven patients with left (left bundle branch block) and four patients with right bundle branch block (right bundle branch block) before and during CRT using biventricular and His-bundle pacing. RESULTS: The acquired activation maps reflect the activation sequence under the tested conditions. e-DYS decreased considerably more than QRS duration, during both biventricular pacing (-50% vs -8%) and His-bundle pacing (-77% vs -13%). While biventricular pacing slightly increased Vd, His-bundle pacing reduced Vd significantly (+11% vs -36%), indicating the contribution of the fast conduction system. Optimization of biventricular pacing by adjusting VV-interval showed a decrease of e-DYS from 102 to 36 ms with only a small Vd increase and QRS duration decrease. CONCLUSIONS: The UHF-ECG technique provides novel information about electrical activation of the ventricles from a standard ECG electrode setup, potentially improving the selection of patients for CRT and application of CRT.
Keywords: Predictive Value of Tests; časové faktory; senioři; ověření koncepční studie; Aged; Male; funkce levé komory srdeční; His-bundle pacing; lidé; Treatment Outcome; ventricular electrical dyssynchrony; Humans; Heart Failure; prediktivní hodnota testů; Proof of Concept Study; Ventricular Function, Left; Ventricular Function, Right; Heart Rate; blokáda Tawarova raménka; srdeční frekvence; Electrocardiography; senioři nad 80 let; Aged, 80 and over; Cardiac Resynchronization Therapy; Time Factors; ultra-high-frequency ECG; mužské pohlaví; výsledek terapie; Hisův svazek; srdeční selhání; funkce pravé komory srdeční; ženské pohlaví; srdeční resynchronizační terapie; Action Potentials; Female; biventricular pacing; akční potenciály; cardiac resynchronization therapy; Bundle-Branch Block; elektrokardiografie; Bundle of His